Prediction and Analysis of Bitcoin Price using Machine learning and Deep learning models - Karnati, Vinay; Kanna, Lakshmi Dathatreya; Pandey, Trilok Nath; Nayak, Chinmaya Kumar (EAI Endorsed Transactions on Internet of Things, 2024)
High Accessibility and Easy Investment makes Cryptocurrency an important income source for many people. Cryptocurrency is a kind of Digital/Virtual currency which is created using blockchain Technology and is protected by Cryptography. Cryptocurrencies enables users to Accept, Transfer and request the capital between the Users without the requirement of intermediaries such as banks. Now a day many Cryptocurrencies are available across the world such as Bitcoin, Litecoin, Monero, Dogecoin etc. This study is more determined over a very famous and demanding Cryptocurrency known as Bitcoin over the past years. Here, firstly we make an effort to predict the price of bitcoin by examining numerous numbers of parameters that affect the cost of bitcoin. Different kinds of Machine learning models will be used to estimate the price of Bitcoin. This study provides the accuracy and precision of each model that are used in this study and determine the suitable method to estimate the price more accurately.
Keywords: Cryptocurrency; Cryptography; Blockchain; Machine Learning; Bitcoin; Dogecoin; Monero; Litecoin